(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The article examines the scientific and methodological aspects of digitalizing the state land cadastre in Uzbekistan, transforming land rights into a market-based asset, and enhancing the investment attractiveness of territories. In advanced international practice, integrated investment attractiveness indices are primarily based on macroeconomic, institutional, and infrastructural indicators, whereas information on land resources and cadastral data is typically regarded only as a secondary factor [1; 3]. In Uzbekistan, however-where a deep reform of land relations is underway, digital land accounting is being introduced, and the need for making investment decisions at the territorial level is increasing-there is a growing demand for a specialized index grounded in land cadastre indicators [4; 6].